Challenges to the democratization of knowledge: status hierarchies and emerging inequalities in educational opportunities amongst oil palm settlers in Papua New Guinea. - Ryan, S.; Curry, George; Germis, E.; Koczberski, Gina; Koia, M. (Springer, Singapore, 2016)
This chapter examines the educational levels and opportunities among migrant oil palm farming households in the three main oil palm-growing areas of Papua New Guinea (PNG). Whilst average adult education levels in oil palm farming communities are higher than the national average, they are still low given most children do not finish primary school. Moreover, findings indicate that population and income pressures are leading to increasing social and economic stratification within and between families. Inequality is most evident by the fact that children from families without regular access to oil palm income have lower education levels than those children from families living on the same block who regularly receive oil palm income. Stratification as differential educational opportunities is a new phenomenon reflecting greater individualism and the rise of market relations and has considerable development implications particularly for policies aimed at reducing poverty and vulnerability levels in rural PNG.